2016
DOI: 10.1136/thoraxjnl-2015-208208
|View full text |Cite
|
Sign up to set email alerts
|

Infant weight trajectories and early childhood wheezing: the NINFEA birth cohort study

Abstract: Faster growth and larger size in the first 18 months of life are both independently associated with an increased risk of wheezing. These findings suggest that early growth patterns play a role in shaping the occurrence of wheezing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Those that used individual longitudinal childhood growth patterns observed that PWV was associated with a higher risk of asthma at 7 and 10 years of age,4 6 and that size and weight velocity (PWV) but not the time at which PWV occurred, were associated with a higher risk of wheezing at 18 months 10. Using the difference between two growth measurements instead, a study showed that a lower lung function partly explained the association of early weight gain and childhood asthma 22.…”
Section: Discussionmentioning
confidence: 99%
“…Those that used individual longitudinal childhood growth patterns observed that PWV was associated with a higher risk of asthma at 7 and 10 years of age,4 6 and that size and weight velocity (PWV) but not the time at which PWV occurred, were associated with a higher risk of wheezing at 18 months 10. Using the difference between two growth measurements instead, a study showed that a lower lung function partly explained the association of early weight gain and childhood asthma 22.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maternal obesity may lead to metabolic and oxidative alterations in the placenta and the fetus 24 , and increased leptin level and insulin resistance in newborns 26 . Such pronounced changes may partly explain why excessive –or accelerated– weight gain in the first few months or years of life has also been linked to recurrent wheezing and incident asthma 27,28 .…”
Section: Maternal Obesity During Pregnancy and Weight Gain In Early Pmentioning
confidence: 99%
“…Accumulating evidence suggests an association between early growth patterns and wheezing in infancy. Within the NINFEA birth cohort, P opovic et al [9], using a novel modelling approach (SITAR) that allows for mutual adjustment of different aspects of growth, showed that larger size and faster growth over the first 18 months of life, but not the timing of peak weight velocity, were independently associated with an increased risk of wheezing at 18 months of age.…”
Section: Early Life Risk Factors For Wheezing and Asthmamentioning
confidence: 99%